A 3-year review of external proficiency testing, evaluating analytical performance and diagnostic accuracy of HELIOS in detecting autoimmune disorders. - Nayab Zehra; Asif Loya; Hiba Asif; Mudassar Hussain; Hina Maqbool; Umer Nisar (Annals of Clinical Biochemistry: International Journal of Laboratory Medicine, 2026)
Objective: To assess the analytical performance and diagnostic accuracy of an automated analyzer HELIOS in external proficiency testing for diagnosing autoimmune disorders based on antinuclear antibody (ANA) images and titer values. Methods: Total 09 CAP shipments over the period of 03 years were included in our study, comprising of 05 samples in each shipment making a total of 45 samples. All samples were analyzed on HELIOS by the technique of Indirect Immunofluorescence (IFA) having built-in library for ANA image comparison and end point titer estimation. Results: The data showed that there was 100% agreement with the positivity and negativity of the PT samples in detecting autoimmune disorders, however, for ANA pattern agreement, it was an average of 90.3% compared to peer mean. The most frequent ANA pattern in all 3 years was nuclear homogenous (40%) followed by nuclear speckled (32%). However, for end-point titer, there is a huge difference of mutual agreement with the PT peer group showing the lowest harmony of 35.3% in 2022 which was reported with titer of 5120, however peer group reported titer was ≤ 640. Thus, the analyzer has a limitation in evaluating end point titer and it should always be critically evaluated by the pathologist before final approval. Conclusion: HELIOS has an acceptable performance in detecting autoimmune disorders and ANA pattern identification, however, for end-point titer, there were many variations for which manual dilutions should be done in routine for accurate analysis of results. Key Words: Autoimmune disorders, External Proficiency testing, HELIOS, Analytical Performance.